English language as strategies for development in Malaysia: from an instrument of colonial imperialism to an engine for economic growth - Hashim, Rosnani (Japan Society for the Promotion of Science, 2006)
The role of English Language in Malaysia has evolved greatly from being highly dominant during the period of colonialism to an underdog during the early decades of Independence to reemerge dominantly as an important instrument of Internationalization and Globalization at the close of the twentieth century. During the period of colonialism, English education was the only means of higher education and was elitist, causing the Malay majority to fall behind economically. The eruption of the May 13, 1969 racial riot led to major reforms, the most important of which was the conversion from English language to the National Language medium of instruction for national education as an attempt to democratize education and narrow the economic divide across the races. However, events in the 1990s, pressure from globalization and concern over decline in the standard of English Language for the teaching of sciences and mathematics in 2003. This paper examines the issues related to this most recent development and its implications for nation-building in Malaysia.